MAD-MT Score: A Tool to Optimize Patient Selection for Mechanical Thrombectomy in Distal Vessel Occlusions - Huanwen Chen; Dhairya A. Lakhani; Hamza Adel Salim; Marco Colasurdo; Vivek Yedavalli; Basel Musmar; Nimer Adeeb; Davide Simonato; Yan-Lin Li; Muhammed Amir Essibayi; Orabi Hajjeh; Nils Henninger; et al. (Stroke, 2026)
BACKGROUND: Endovascular thrombectomy (EVT) for distal and medium vessel occlusion stroke remains uncertain. We aimed to develop a medium and distal mechanical thrombectomy score integrating clinical need and procedural risk to guide patient selection. METHODS: This retrospective cohort analysis used an international distal and medium vessel occlusion stroke registry spanning the study period of 2017 to 2023. Patients with acute distal and medium vessel occlusion stroke who received medical management (MM) or EVT across 37 stroke centers were included, and those with baseline modified Rankin Scale score of ≥3 or those with missing covariable data were excluded. Multivariable logistic regression identified predictors of poor functional outcome (modified Rankin Scale score >2 at 90 days) in the MM cohort and predictors of EVT failure/complications in the EVT cohort. Predictors of poor outcome on MM were assigned positive weights (clinical need); predictors of EVT failure/harm were assigned negative weights (procedural risk). The medium and distal mechanical thrombectomy score summed these weighted points. Interaction analysis assessed the heterogeneity of EVT effect by score. RESULTS: A total of 1217 patients were identified, and 1007 were included (EVT: 822, MM: 185; median age 73 years; 41% female). Higher National Institutes of Health Stroke Scale score (+1 per point) and lack of intravenous thrombolysis (+7) predicted poor MM outcomes. In the EVT cohort, older age (−1 per 15 years above 25), absence of hypertension (−2), and absence of atrial fibrillation (−2) predicted failure/complications. The medium and distal mechanical thrombectomy score (range −8 to 49) significantly modified EVT effect versus MM ( P interaction =0.048). In high-score patients (≥15; n=293), EVT yielded a better 90-day modified Rankin Scale score than MM (median, 3 versus 4; P =0.009). Conversely, in low-score patients (